Association Between 20-Year Trajectories of Nonoccupational Physical Activity From Midlife to Old Age and Biomarkers of Cardiovascular Disease: A 20-Year Longitudinal Study of British Men. Issue 11 (14th August 2018) - Aggio, Daniel; Papachristou, Efstathios; Papacosta, Olia; Lennon, Lucy T; Ash, Sarah; Whincup, Peter H; Wannamethee, S Goya; Jefferis, Barbara J
Abstract: The trajectories of physical activity (PA) from midlife into old age and their associations with established and novel cardiovascular disease (CVD) risk factors in later life remain unclear. This study examined associations between 20-year nonoccupational PA trajectories and a range of CVD biomarkers at ages 60–79 years. We used data from a sample of 3, 331 men (mean baseline age = 50.2 ± 5.8 years) recruited in 1978–1980, with follow-up after 12, 16, and 20 years, reporting habitual nonoccupational PA at each wave. At the 20-year follow-up, surviving men attended a physical examination and provided a fasting blood sample. Group-based trajectory modeling was used to identify trajectories. Adjusted regression analyses examined the association between trajectory-group membership and several cardiometabolic, cardiac, and inflammatory markers at follow-up. Three distinct 20-year trajectories were identified: low/decreasing (21.3%), light/stable (51.8%), and moderate/increasing (27.0%). Compared with the low/decreasing group, membership in the light/stable and moderate/increasing trajectory groups was associated with a more favorable cardiometabolic profile and lower levels of inflammation and endothelial dysfunction. Although following a moderate-increasing PA trajectory was most favorable, more modest but sustained doses of PA into old age may be sufficient to lower CVD risk.